Interalar distance to estimate the combined width of the six maxillary anterior teeth in oral rehabilitation treatment. - Gomes VL; Gonçalves LC; Costa MM; De Lima Lucas B (Journal of Esthetic & Restorative Dentistry, 2009)
Statement of the Problem: The face's architecture of dentate subjects has been studied to find a reliable guide for the selection of artificial anterior teeth. However, there is no consensus of data regarding a reference to estimate the width of artificial teeth. Purpose: The purpose of this study was to analyze whether there is a consistent relationship between the interalar distance (IAD) and the combined mesiodistal width of the six maxillary anterior teeth. Methods: Standardized digital photographs of 81 dentate Brazilian subjects were included in the sample. They were 37 men and 44 women (age 17 to 33). Through image processing software, the IAD and the distance between the tips of the maxillary canines were measured when viewed from the frontal aspect. Accurate casts were made to quantify the distance between the distal surfaces of the maxillary canines on a curve, by use of a flexible millimeter ruler. Nonparametric statistics were performed to analyze the results (p < 0.05). Results: The IAD when compared with the width of the six maxillary anterior teeth, on a straight line and on a curve, presented a ratio of 0.914 and of 1.305, respectively. The Wilcoxon test showed no significant difference between the calculated width values and the mesiodistal width measured on a curve and on a straight line (p = 0.986). Conclusion: The IAD, when increased by 31% of its value, can suggest the circumferential distance of the six maxillary anterior teeth. CLINICAL SIGNIFICANCE The width of the nose, when measured in digital photographs, can be utilized as a reliable guide for the selection of the maxillary anterior teeth width. It can improve the esthetic result of the oral rehabilitation treatment for the edentulous patient by offering a natural dentofacial relation.